Analisis Studi Kelayakan Bisnis Pemanfaatan Limbah Agribisnis Menjadi Energi Alternatif di Kecamatan Tanah Jawa Kabupaten Simalungun - Insandi, Arief Muhazir; Kuswardhani, Retna Astuti; Sibuea, M. Buhari (Universitas Medan Area, 2019)
This study aims to determine the business feasibility of utilizing agribusiness waste (rice husks and corncobs) into alternative energy in Tanah Jawa District, Simalungun Regency. This research was conducted for six months from June to December 2016. This study analyzed the market and marketing of rice husk waste and corn cobs into charcoal briquettes and analyzed the feasibility of investment in the construction of charcoal briquette installations in Tanah Jawa District, Simalungun Regency. The samples in this study were entrepreneurs of rice refineries and corn refineries spread in Tanah Jawa District, Simalungun Regency. The sampling method used is the saturated sample method, which is a deliberate sampling process wherein because the population is small, all populations are sampled. Samples from rice refineries were 2 refineries, while samples from corn refineries were 4 refineries. Data analysis methods use income analysis, business feasibility financial analysis, and sensitivity analysis. The results showed that the utilization of rice husk waste and corncobs into alternative energy (charcoal briquettes) in Tanah Jawa District, Simalungun Regency was feasible and profitable to be cultivated.